DLP 3D bio printing the cornea using decellularised extracellular matrix (dECM) - Ahamed Ebrahim S/O Mohamed Jameel (Nanyang Technological University, 2024)
Tissue engineering has been transformed by the arrival of 3D bioprinting, which provides innovative approaches to organ and tissue regeneration. In this study, we investigate the use of decellularized extracellular matrix (dECM) as a bioink in 3D bioprinting technology for the fabrication of corneal tissue. Given its complicated structure and cellular composition, the cornea faces exceptional barriers for bioprinting as a complex and highly tailored tissue. Our methodology involves the decellularization of human and animal corneal tissues to obtain a scaffold rich in extracellular matrix ECM components, devoid of cellular elements. This dECM is then processed into a bioink suitable for 3D bioprinting. We employ advanced bioprinting techniques to precisely deposit the dECM bioink, layer by layer as well as continuous method, replicating the native corneal architecture. The bio fabricated corneal construct is subsequently evaluated for structural integrity and biomechanical properties. Initial findings indicate the achievement of successful bioprinting of a corneal construct mirroring the curvature of the native cornea. Printability assessments illustrate that DLP bioprinting enables precise control over surface features with high resolution. Optical evaluations unveil encouraging transparency levels comparable to those of natural corneas. This study demonstrates the viability of 3D bioprinting the cornea using decellularized extracellular matrix, which represents a breakthrough in the field of tissue engineering. The new method has the potential to address the increasing need for corneal transplantation, create customized corneal implants, and get around the drawbacks of using conventional donor tissues. Further optimization and in-depth in vivo studies are warranted to validate the long-term functionality and integration of the bio printed corneas in a clinical context.